Research methods for sport management - Skinner, James 1964-; Smith, Aaron 1972-; Read, Daniel; Burch, Lauren; Mueller, Jacqueline (Routledge, 2025)
Now in a fully revised and updated second edition, Research Methods for Sport Management provides a complete introduction to qualitative, quantitative, and mixed methods for sport management students and practitioners. Full of real-world case studies, data, and examples, and including international perspectives throughout this book to help the reader understand the challenges of research in different social and cultural contexts, this book links theory to practice, highlighting the importance of research skills in the contemporary sport industry. This book outlines an eight-step research framework that makes the research process easy to understand and that can be followed by beginners and built upon by more advanced researchers. It covers the full research process from research design and literature review to data analysis and report writing, with a strong emphasis throughout this book on new digital, online, and social media methods. This new edition includes extended coverage of topics such as research ethics, gender in research, intersectional research, Web 3.0, data visualization, research impact, and advanced statistical techniques, and considers the differing requirements of sport-related research across the private, public, and not-for-profit sectors. With improved features to enhance teaching and learning, including a research f low chart, review questions, topical case studies, and PowerPoint slides, this is an essential textbook for any research methods course taken as part of a degree course in sport business and management, sport development, or sport marketing, and an invaluable toolkit for any managers, leaders, or analysts working in the sport industry
Keywords: bisacsh / BUSINESS & ECONOMICS / Industries / Park & Recreation Management; bisacsh / SPORTS & RECREATION / General; Management; Methode; Sport